Surface AMP deaminase 2 as a novel regulator modifying extracellular adenine nucleotide metabolism. Issue 7 (23rd June 2021) - Ehlers, Lisa; Kuppe, Aditi; Damerau, Alexandra; Wilantri, Siska; Kirchner, Marieluise; Mertins, Philipp; Strehl, Cindy; Buttgereit, Frank; Gaber, Timo
Abstract: Adenine nucleotides represent crucial immunomodulators in the extracellular environment. The ectonucleotidases CD39 and CD73 are responsible for the sequential catabolism of ATP to adenosine via AMP, thus promoting an anti‐inflammatory milieu induced by the "adenosine halo". AMPD2 intracellularly mediates AMP deamination to IMP, thereby both enhancing the degradation of inflammatory ATP and reducing the formation of anti‐inflammatory adenosine. Here, we show that this enzyme is expressed on the surface of human immune cells and its predominance may modify inflammatory states by altering the extracellular milieu. Surface AMPD2 (eAMPD2) expression on monocytes was verified by immunoblot, surface biotinylation, mass spectrometry, and immunofluorescence microscopy. Flow cytometry revealed enhanced monocytic eAMPD2 expression after TLR stimulation. PBMCs from patients with rheumatoid arthritis displayed significantly higher levels of eAMPD2 expression compared with healthy controls. Furthermore, the product of AMPD2—IMP—exerted anti‐inflammatory effects, while the levels of extracellular adenosine were not impaired by an increased eAMPD2 expression. In summary, our study identifies eAMPD2 as a novel regulator of the extracellular ATP‐adenosine balance adding to the immunomodulatory CD39‐CD73 system.